2021
DOI: 10.46298/lmcs-17(3:22)2021
|View full text |Cite
|
Sign up to set email alerts
|

The Shapley Value of Tuples in Query Answering

Abstract: We investigate the application of the Shapley value to quantifying the contribution of a tuple to a query answer. The Shapley value is a widely known numerical measure in cooperative game theory and in many applications of game theory for assessing the contribution of a player to a coalition game. It has been established already in the 1950s, and is theoretically justified by being the very single wealth-distribution measure that satisfies some natural axioms. While this value has been investigated in several … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
52
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(53 citation statements)
references
References 32 publications
1
52
0
Order By: Relevance
“…Following earlier notions of formal causality by Halpern and Pearl [15], Salimi et al [27] proposed the causal effect: assuming endogenous facts are randomly removed independently and uniformly, what is the difference in the expected query answer between assuming the presence and the absence of f ? A recent framework has proposed to adopt the Shapley value to the task [20].…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Following earlier notions of formal causality by Halpern and Pearl [15], Salimi et al [27] proposed the causal effect: assuming endogenous facts are randomly removed independently and uniformly, what is the difference in the expected query answer between assuming the presence and the absence of f ? A recent framework has proposed to adopt the Shapley value to the task [20].…”
Section: Introductionmentioning
confidence: 99%
“…In the framework of Livshits et al [20], query answering is viewed as a cooperative game where the players are the database facts and the utility function is the query answer, in the case of aggregate queries, or 0/1 in the case of Boolean queries. They showed that the (precise or approximate) evaluation of the Shapley value on common aggregate queries amounts to the evaluation of the Shapley value for a Boolean query.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations